2017
DOI: 10.1186/s12868-017-0337-4
|View full text |Cite
|
Sign up to set email alerts
|

Selenium suppresses glutamate-induced cell death and prevents mitochondrial morphological dynamic alterations in hippocampal HT22 neuronal cells

Abstract: BackgroundPrevious studies have indicated that selenium supplementation may be beneficial in neuroprotection against glutamate-induced cell damage, in which mitochondrial dysfunction is considered a major pathogenic feature. However, the exact mechanisms by which selenium protects against glutamate-provoked mitochondrial perturbation remain ambiguous. In this study glutamate exposed murine hippocampal neuronal HT22 cell was used as a model to investigate the underlying mechanisms of selenium-dependent protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 57 publications
3
17
0
1
Order By: Relevance
“…The results obtained herein also demonstrated an insignificant effect of Se treatment on hippocampal level of glutamate of treated CRS group, nevertheless, studies recorded that Se may indirectly counteracted glutamate induced neurotoxic insult in hippocampal neurons by different mechanism [80] , and that Se deficiency may increase the susceptibility to neurotoxic insults of glutamate [81] , these data may give the assumption that the effect of se on glutamate toxicity may be mediated indirectly through antagonizing its toxic effects rather than affecting its basal level.…”
supporting
confidence: 54%
“…The results obtained herein also demonstrated an insignificant effect of Se treatment on hippocampal level of glutamate of treated CRS group, nevertheless, studies recorded that Se may indirectly counteracted glutamate induced neurotoxic insult in hippocampal neurons by different mechanism [80] , and that Se deficiency may increase the susceptibility to neurotoxic insults of glutamate [81] , these data may give the assumption that the effect of se on glutamate toxicity may be mediated indirectly through antagonizing its toxic effects rather than affecting its basal level.…”
supporting
confidence: 54%
“…Mitochondria are increasingly recognized as key players in acquired kidney diseases (9). The structure of mitochondria is mainly regulated by cycles of fusion and fission (28). The role of mitochondrial fission in apoptosis has been confirmed by different laboratories in various apoptotic models (4).…”
Section: Discussionmentioning
confidence: 98%
“…Selenium was found to protect against neuronal hyperexcitability results from excessive production of glutamate. 83 In the same context, Ma et al 84 showed that selenium blocked neuronal loss and protected the hippocampal HT22 nerve cells against glutamate-induced mitochondrial dysfunction.…”
Section: Dovepressmentioning
confidence: 99%